2013
DOI: 10.1213/ane.0b013e31826d37c5
|View full text |Cite
|
Sign up to set email alerts
|

Early Developmental Exposure to Volatile Anesthetics Causes Behavioral Defects in Caenorhabditis elegans

Abstract: BACKGROUND Mounting evidence from animal studies shows that anesthetic exposure in early life leads to apoptosis in the developing nervous system. This loss of neurons has functional consequences in adulthood. Clinical retrospective reviews have suggested that multiple anesthetic exposures in early childhood are associated with learning disabilities later in life as well. Despite much concern about this phenomenon, little is known about the mechanism by which anesthetics initiate neuronal cell death. Caenorhab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 26 publications
5
37
1
Order By: Relevance
“…The plates were divided into 3 regions in a modification of the technique described by Bargmann [3, 18]. One region contained an attractant (a 20ul spot of OP50) while the opposite region contained no attractant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The plates were divided into 3 regions in a modification of the technique described by Bargmann [3, 18]. One region contained an attractant (a 20ul spot of OP50) while the opposite region contained no attractant.…”
Section: Methodsmentioning
confidence: 99%
“…These pathological changes were accompanied by a learning defect that persisted into adulthood in the rat. It is now established that, from nematodes [3] to rodents [1, 4, 5] and to primates [6, 7], volatile anesthetics in isolation are capable of inducing neurodegeneration in the developing nervous system [811]. It remains unclear how great a risk anesthetic exposure poses to the newborn human at clinical doses and lengths of time [9, 12, 13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the safety of anesthesia in this population is a concern and prior retrospective studies have noted a correlation between anesthesia exposure and learning disabilities 1,2 . In addition, various animal models have shown that early anesthetic exposure results in significant long-term behavioral deficits 3-5 .…”
Section: Introductionmentioning
confidence: 99%
“…Infant rats were given an anesthetic of isoflurane, nitrous oxide and midazolam and were subsequently found to have significant neuronal cell death and lasting memory impairment (10). Since then there have been many animal studies demonstrating this effect in different species (5,11), with different anesthetic agents (12)(13)(14)(15), and affecting different domains of cognition (16)(17)(18). Early studies focused on anesthesia-induced apoptosis (10,19), however the developing brain possesses neurons in excess and normal apoptosis is present during development (20,21).…”
mentioning
confidence: 99%